A relationship between spinal new bone formation in ankylosing spondylitis and the sonographically determined Achilles tendon enthesophytes - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (SPRINGER HEIDELBERG, 2016)
Spinal new bone formation is a major but incompletely understood manifestation of ankylosing spondylitis (AS). We explored the relationship between spinal new bone formation and ultrasound (US)-determined Achilles enthesophytes to test the hypothesis that spinal new bone formation is part of a generalized enthesis bone-forming phenotype. A multicenter, case control study of 225 consecutive AS patients and 95 age/body mass index (BMI) matched healthy controls (HC) was performed. US scans of Achilles tendons and cervical and lumbar spine radiographs were obtained. All images were centrally scored by one investigator for US and one for radiographs, blinded to medical data. The relation between syndesmophytes (by modified Stoke Ankylosing Spondylitis Spine Score (mSASSS) and the number of syndesmophytes) and enthesophytes (with a semi-quantitative scoring of the US findings) was investigated. AS patients had significantly higher US enthesophyte scores than HCs (2.1(1.6) vs. 1.6(1.6); p = 0.004). The difference was significant in males (p = 0.001) but not in females (p = 0.5). The enthesophyte scores significantly correlated with mSASSS scores (rho = 0.274, p < 0.0001) with the association even stronger in males (enthesophyte scores vs. mSASSS rho = 0.337, p < 0.0001). In multiple regression analysis, age, BMI, enthesophyte scores and disease duration were significantly associated with syndesmophytes in males, and keeping all other variables constant, increasing US enthesophyte scores increased the odds of having syndesmophytes by 67 %. Male AS patients that have more severe US-determined Achilles enthesophyte also associated spinal syndesmophytes suggesting a bone-forming gender-specific phenotype that could be a useful marker predicting of new bone formation.
Keywords: Ankylosing spondylitis; Bone-forming phenotype; Ultrasonography